Phenotypic and Genotypic Characterization of Extended-spectrum beta-lactamase Producing Escherichia coli and Klebsiella species Isolated from a Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Medical Microbiology, 2016)
This study was conducted to determine the presence of ESBL producing Escherichia coli and Klebsiella species in a tertiary care hospital of Bangladesh, as well as to observe the patterns of antibiotic resistance and antibiotic resistance genes among them. A total of 166 Escherichia coli,Klebsiella pneumoniae and Klebsiella oxytoca were isolated from urine, wound swab, pus, sputum and blood samples of patients of Dhaka Medical College Hospital. Antibiotic susceptibility test wasperformed by disk-diffusion technique. ESBL producers were detected phenotypically by Double-disk synergy (DDS) test. Genotypically ESBL genes (blaCTX-M-15, blaOXA-1) among the ESBL producers with presence of class 1 integron among them were detected by PCR. Eighty seven (52.41%) ESBL producers were detected by DDS test. CTX-M-15 (80.46%) was the dominant genotype in ESBL producing strains detected by PCR. Class 1 integron was found in 58 (66.67%) of the phenotypic positive ESBL producers. The results of this study showed high proportion of ESBL producing Escherichia coli and Klebsiella species in Bangladesh.Bangladesh J Med Microbiol 2016; 10 (2): 4-8